Man-Machine-Environment System Engineering: Proceedings of the 21st International Conference on MMESE Commemorative Conference for the 110th Anniversary of Xuesen Qian$1 (Bs Birth and the 40th Anniversary of Founding of Man-Machine-Environment System Engineering /s - Long, Shengzhao; Dhillon, Balbir S.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
Man-Machine-Environment System Engineering: Proceedings of the 21st Conference on MMESE is the academic showcase of best research papers selected from more than 500 submissions each year. From this book reader will learn the best research topics and the latest development trend in MMESE design theory and other human-centered system application. MMESE focus mainly on the relationship between Man, Machine and Environment. It studies the optimum combination of man-machine-environment systems. In the system, the Man means the working people as the subject in the workplace (e.g. operator, decision-maker); the Machine means the general name of any object controlled by the Man (including tool, Machinery, Computer, system and technology), the Environment means the specially working conditions under which Man and Machine occupy together(e.g. temperature, noise, vibration, hazardous gases etc.). The three goals of the optimization of the system are safety, efficiency and economy. In 1981 with direct support from one of the greatest modern Chinese scientists, Qian Xuesen, Man-Machine-Environment System Engineering (MMESE), the integrated and advanced science research topic was established in China by Professor Shengzhao Long. In the letter to Shengzhao Long, in October 22nd, 1993, Qian Xuesen wrote: (3z(BYou have created a very important modern science subject and technology in China!(3y(B. .s
Research on the Man Character -- Research on the Machine Character -- Research on the Environment Character -- Research on the Man-Machine Relationship -- Research on the Man-Environment Relationship -- Research on the Machine-Environment Relationship -- Research on the Overall Performance of Man-Machine-Environment System -- Theory & Application Research of the MMESE.
Keywords: Manufactures; Environmental Psychology; Psychology, Industrial; Artificial intelligence; Industrial Management; Aerospace engineering; Astronautics; Machines, Tools, Processes; Environmental Psychology; Industrial Psychology; Artificial Intelligence; Industrial Management; Aerospace Technology and Astronautics; Human-machine systems -- Congresses